Individual and Community Characteristics of the Opioid Crisis in West Virginia - Hodges, Collin D. (Journal of drug issues, 2024)
In this paper we examine the changing demographics of overdose deaths in West Virginia based upon death certificate and economic data in West Virginia for the years 2001–2016. During the period under study, opioid overdose deaths accounted for 7% of deaths overall, and a significant number of premature deaths. Those affected were an average of 41 years old and were more likely to be unmarried and less than college educated. Eighty percent were employed at the time of death and individual employment in specific industries was associated with an increased risk of opioid overdose death. Previous state and national level policies attempting to address the opioid crisis may have lagged behind the data trends for this time period and thus been less effectual. Future policies intended to ameliorate the harms associated with the opioid crisis should reflect current data trends to help the communities and individuals at high risk for overdose death.